Baudrillard for architects - Proto, Francesco (Abingdon, Oxon ; New York : Routledge, 2020)
"The impact of Baudrillard's thought on architecture has often been marginalized due to his work being so difficult to read, but this book makes accessible an explanation of Baudrillard's philosophical concepts through the prism of architecture, showing how they are relevant to architecture today. Presenting an introductory but in-depth assessment and critique of Baudrillard's interest in architecture, key concepts such as the object and the code, seduction and hyper-reality, obscenity and terrorism, and cultural consumption are highlighted here. The book emphasises how the mutual concerns of cultural theory and architecture provide a fruitful ground for debate. This is an approach which students and practitioners in architecture will benefit immensely from - focusing on the contradictions inherent in contemporary architecture in the light of Baudrillard's work"--
OCLC-licensed vendor bibliographic record.
Keywords: Baudrillard, Jean, -- 1929-2007.; Architecture -- Philosophy; ARCHITECTURE / General; ARCHITECTURE / Criticism; PHILOSOPHY / General